2004
DOI: 10.1159/000081103
|View full text |Cite
|
Sign up to set email alerts
|

The <i>TP53</i> Tumor Suppressor Gene and Melanoma Tumorigenesis: Is There a Relationship?

Abstract: Mutations in the TP53 gene are found in about 11% of melanomas. Although nearly 600 papers have been published with varying degrees of consensus, there does not appear to be any comparable analysis that facilitates more than a glimpse into the role of p53 in melanomagenesis. This article reviews p53 alterations (at the gene and protein levels) in melanocytic skin lesions and discusses the following points: (i) p53 alterations commence as early as at the stage of benign and dysplastic nevi; (ii) these alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…These findings are in line with those reported in the literature. 40 Our results showed that the number of securin-and p53-positive cells are significantly correlated, and that in some melanomas, overexpression of both proteins occurred in the same neoplastic cells. Although we have no firm in vitro data, we can speculate that, in analogy with other cancers, hPTTG1 overexpression in melanoma modulates the transcriptional activity of p53, resulting in impairment of apoptosis.…”
Section: Discussionsupporting
confidence: 51%
“…These findings are in line with those reported in the literature. 40 Our results showed that the number of securin-and p53-positive cells are significantly correlated, and that in some melanomas, overexpression of both proteins occurred in the same neoplastic cells. Although we have no firm in vitro data, we can speculate that, in analogy with other cancers, hPTTG1 overexpression in melanoma modulates the transcriptional activity of p53, resulting in impairment of apoptosis.…”
Section: Discussionsupporting
confidence: 51%
“…p53 expression in melanocytic skin lesions varies considerably in different studies from a small percentage of positively stained cells (57) to Ͼ50% of tumor cells (58,59). However, different studies support the notion that p53 alterations may play a role in later stages of melanoma development and progression (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of p53 in regulation of IGF-1R seems to be more complex and probably also involves post-transcriptional mechanisms (Girnita et al, 2000;Lee et al, 2003). This can be exemplified by malignant melanoma cells, most often harbouring wild-type p53 (Hussein, 2004), which exhibit overexpression of IGF-1R. Upon inhibition of wild-type p53 in these cells, they surprisingly responded with a drastic IGF-1R downregulation and cell death (Girnita et al, 2000).…”
Section: Interactions Between Igf-1r and Oncogenesmentioning
confidence: 99%